2011
DOI: 10.1080/17470919.2011.557245
|View full text |Cite
|
Sign up to set email alerts
|

I feel your pain: Emotional closeness modulates neural responses to empathically experienced rejection

Abstract: Empathy is generally thought of as the ability to share the emotional experiences of others. In scientific terms, this is usually operationalized as an ability to vicariously feel others' mental and emotional experiences. Supporting this account, research demonstrates that watching others experience physical pain activates similar brain regions to the actual experience of pain itself. First-hand experience of social rejection also activates this network. The current work extends these findings by examining whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 53 publications
1
73
0
2
Order By: Relevance
“…The genuine emotional distress conveyed by TRC victims probably accounts for activation in these areas, as well as those in the amygdala and PAG, even though victims were strangers. Previous studies have mostly detected activation in affective pain areas when those in distress were emotionally close (Beeney et al , 2011; Meyer et al , 2013). Our data suggest that it is not emotional closeness per se, but rather emotional salience that lead to activation in these areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genuine emotional distress conveyed by TRC victims probably accounts for activation in these areas, as well as those in the amygdala and PAG, even though victims were strangers. Previous studies have mostly detected activation in affective pain areas when those in distress were emotionally close (Beeney et al , 2011; Meyer et al , 2013). Our data suggest that it is not emotional closeness per se, but rather emotional salience that lead to activation in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…These regions relate to the representation of affective distress associated with the first-hand experience of pain, although some studies suggest they are not specific to pain perception (Mouraux et al , 2011; Salomons et al , 2016). In contrast, studies exploring empathy for social pain have found activation in the ‘mentalizing network’ (Masten et al , 2011; Zaki and Ochsner, 2012), although activation in areas associated with both the affective (Beeney et al , 2011; Meyer et al , 2013) and sensory discriminative (Novembre et al , 2015) aspects of pain processing have also been observed.…”
Section: Introductionmentioning
confidence: 88%
“…While all these paradigms attempt to directly exclude the participant, a few other tasks aim to elicit feelings of exclusion less directly, or even specifically examine the neural correlates of witnessing others being excluded. For example, studies have examined neural responses to rejection cues in the form of pictures and words related to social exclusion (Premkumar et al, 2012; Sebastian et al, 2010a), or used Cyberball to show others/peers being excluded (Beeney et al, 2011; Masten et al, 2013; 2011c; Meyer et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Symmetrical dipoles were fitted in the lingual gyrus (x=±7, y=-79, z=5), because left lingual gyrus activation is increased during rejection than acceptance scenes and posterior P1 amplitude is sourced to the lingual gyrus during face processing in young adolescents (Wong et al, 2009). Symmetrical dipoles were fitted in the temporal pole (x=±36, y=14, z=-26), because the temporal pole is activated during evaluation of social feedback as rejection from others and when imputing other people's emotional states (Beeney et al, 2011;Jimura et al, 2010;Korn et al, 2012) those ERP components for which there was a main effect of social interaction type. If both ERP amplitude and RS were found to correlate with positive schizotypy, then a hierarchical regression analysis was performed to determine the independent contributions of the rejection-related amplitude/dipole moment at that ERP component and RS to schizotypy variance.…”
Section: Eeg Processing and Analysismentioning
confidence: 99%